Long-term contamination by non-native fish assemblages in a Neotropical floodplain. - Luis Artur Valões Bezerra; Simone Libralato; Jan Kubečka; Andre Andrian Padial (PLoS ONE)
Biological invasions are a major threat to biodiversity in species-rich regions. Therefore, it is important to understand mechanisms behind the long-term establishment of non-native fish species in aquatic environments in the Neotropical region. Here, we associated fish biomass, species richness, and the proportion of non-native species (contamination and Kempton's indices) to quantify the non-native pressure over fish biodiversity in lakes and rivers of the Parana River floodplain, seasonally, from 2000 to 2017. We divided species into native and non-native assemblages sampled in spatio-temporal gradients. Temporal trends were examined using linear regressions and generalised additive models. Fish biomass in gillnets increased for both native and non-native fish species, but their Kempton indices were inversely correlated. Extinction of native species occurred locally with biotic differentiation of non-native species in lakes, rivers, and ecosystem contamination. A constant increase in fish biomass resulted in overwhelming biodiversity of non-natives at the end of the time series evaluated. Native biotic resistance to introductions was not detected in deterministic trends. The observed patterns were consistent with previous studies showing native biotic homogenisation and extinction of species in response to biological invasions, landscape fragmentation, and riverine impoundments. Increases in abundance and species richness of non-native fish were the biodiversity drivers that resulted in non-native species outweighing native species in the Parana floodplain.